Somatic Variation of T-Cell Receptor Genes Strongly Associate with HLA Class Restriction. - Paul L Klarenbeek (PLoS ONE, 2015)
Every person carries a vast repertoire of CD4+ T-helper cells and CD8+ cytotoxic T cells for a healthy immune system. Somatic VDJ recombination at genomic loci that encode the T-cell receptor (TCR) is a key step during T-cell development, but how a single T cell commits to become either CD4+ or CD8+ is poorly understood. To evaluate the influence of TCR sequence variation on CD4+/CD8+ lineage commitment, we sequenced rearranged TCRs for both α and β chains in naïve T cells isolated from healthy donors and investigated gene segment usage and recombination patterns in CD4+ and CD8+ T-cell subsets. Our data demonstrate that most V and J gene segments are strongly biased in the naïve CD4+ and CD8+ subsets with some segments increasing the odds of being CD4+ (or CD8+) up to five-fold. These V and J gene associations are highly reproducible across individuals and independent of classical HLA genotype, explaining ~11% of the observed variance in the CD4+ vs. CD8+ propensity. In addition, we identified a strong independent association of the electrostatic charge of the complementarity determining region 3 (CDR3) in both α and β chains, where a positively charged CDR3 is associated with CD4+ lineage and a negatively charged CDR3 with CD8+ lineage. Our findings suggest that somatic variation in different parts of the TCR influences T-cell lineage commitment in a predominantly additive fashion. This notion can help delineate how certain structural features of the TCR-peptide-HLA complex influence thymic selection.